Stakeholder behavior, relationship building practices and stakeholder management in Public Private Partnership Projects in Uganda - Mwesigwa, Rogers; Ntayi, Joseph; Bagire, Vincent; Munene, John C. (Makerere Business Journal, 2018)
The purpose of this paper is to provide evidence of the influence of stakeholder behaviour and relationship building practices on stakeholder management in Public Private Partnership (PPP) projects.in Uganda Design/Methodology/approach - We study 115 PPP projects in Uganda using a cross sectional design. Data was collected using a questionnaire survey and analyzed using Statistical Package for Social Sciences. Findings - Results indicate that stakeholder behaviour and relationship building practices are significant predictors of stakeholder management in PPP projects. The interaction (multiplication) of understanding of stakeholders’ behaviours and building relationships among them explains more of the variance in overall project management for project success than the direct influence of understanding of stakeholders’ behaviours or relationship building on their own. Implications - In order to manage stakeholders in PPP projects, there is need to build strong stakeholder relationships at the same time understanding project stakeholder behaviours. Originality - We adduce evidence of the efficacy of understanding stakeholder behaviours and designing appropriate relationship building practices for better stakeholder management.
Keywords: Public private partnership projects; Stakeholder management; Stakeholder behaviour; Relationship building practices